Study on an Interactive System for Conceptual and Basic Design of Machine Tool Structure - Zhangyong YU; Keiichi NAKAMOTO; Tohru ISHIDA; Yoshimi TAKEUCHI (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2010)
This paper presents the improvement of design efficiency of machine tool structure in the conceptual and basic design stage. An interactive system has been developed for designing machine tool structure in this study. The key point in the interactive system is that a set of beam elements are assumed to compose the total structure of machine tool because it is easy to analyze the static, dynamic and thermal features. In this interactive system, a conversion procedure also has been developed. By using this conversion procedure, the selected beam structure of machine tool can be converted to an actual structure, completing conceptual and basic design. Consequently, using the interactive system allow, designers can complete the machine tool structure design in a shorter time with higher efficiency. The goal of the interactive system is to assist designers to quantitatively and quickly select a superior machine tool structure.